2021
DOI: 10.3390/rs13102011
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of GPR-Based Rebar Diameter Estimation Using YOLO-v3

Abstract: As the frequency of earthquakes has increased in Korea in recent years, designing earthquake-resistant facilities has been increasingly emphasized. Structures constructed with rebars are vulnerable to shaking, which reduces their seismic performance and may result in damage to human life and property. Because the construction of facilities requires the maintenance of sub-constructions, such as by cutting rebars or compensating for missing rebars, information on rebar diameter is required. In this study, the YO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The YOLO framework has been successfully used in several diverse applications of civil engineering, such as pedestrian detection [46], real-time face detection [47], license plate detection [48], spilled load detection on freeways [49], pothole detection [50], traffic load distribution detection [51], worker and heavy construction equipment identification on site [52], building component identification [53], rebar diameter estimation [54], building footprint estimation [55], traffic management [56], pavement distress detection [57], crack detection [58][59][60][61], and maintenance [62][63][64]. The following sections describe the details of the structure of YOLOv5.…”
Section: Proposed Model For the Detection Of Cracks And Determination...mentioning
confidence: 99%
“…The YOLO framework has been successfully used in several diverse applications of civil engineering, such as pedestrian detection [46], real-time face detection [47], license plate detection [48], spilled load detection on freeways [49], pothole detection [50], traffic load distribution detection [51], worker and heavy construction equipment identification on site [52], building component identification [53], rebar diameter estimation [54], building footprint estimation [55], traffic management [56], pavement distress detection [57], crack detection [58][59][60][61], and maintenance [62][63][64]. The following sections describe the details of the structure of YOLOv5.…”
Section: Proposed Model For the Detection Of Cracks And Determination...mentioning
confidence: 99%
“…Among various object detection techniques of region-based CNNs (R-CNNs), YOLO-v3 [29] demonstrates object detection speed that is more than 100 times faster than that of Fast R-CNNs [30], thanks to two model structure updates from YOLO-v1 [31]. In addition, the YOLO-v3 model has the advantage of being able to learn universal objects well, so it has been recently adopted in various object recognition models in the construction field [32][33][34].…”
Section: Object Detection and Trackingmentioning
confidence: 99%
“…Kim et al [17] proposed a road defect recognition method based on a convolutional neural network (CNN), which uses CNN to locate road defects after GPR image thresholding. Park [18] studied the performance of the YOLOv3 algorithm in real-time prediction of rebar diameters in facilities, and the result showed that the method can achieve real-time prediction. Yang et al [19] showed that YOLOv5l can achieve the highest detection accuracy and effectively detected the coal fire range, providing a basis for coal fire disaster control.…”
Section: Introductionmentioning
confidence: 99%